A Meta-Analysis of the Human Gut Mycobiome Using Internal Transcribed Spacer Data - Zeming Zhang; Yining Zhang; Qixiang Yuan; Zuoyi Wang; Songnian Hu; Peng Yin; Zilong He (Microorganisms)
The intestinal mycobiome is closely related to human health. There have been several reports investigating the association between the gut fungi and disease, but there is still a lack of overall assessment of the human gut mycobiome. Here, we performed a meta-analysis based on 2372 ITS (Internal Transcribed Spacer) data collected publicly online. We found that the mycobiome diversity of human gut fungi varies significantly across diseases by using EasyAmplicon, and these fungi are mainly composed of three genera, Saccharomyces, Candida, and Aspergillus. In addition, we performed the construction of disease prediction models based on ITS data by using the random forest model and verified the generalization ability of the models. We hope that our results will provide strong support for subsequent studies of the intestinal mycobiome.